A fast mesh deformation method for marine propeller flow. Issue 10 (26th November 2018) - Zhong, Jize; Xie, Zhiqiang; Wang, Chunxu; Shen, Du; Wang, Hao
ABSTRACT: A fast mesh deformation method for propeller flow is developed based on the elastic solid method. The flow field of a propeller is assumed to be fulfilled with a kind of pseudo elastic solid which does not influence the flow. The vibration equation for the propeller blade-pseudo elastic solid system is derived. During fluid-structure coupling, the nodal displacement for the blade and the flow mesh is computed by modal superposition of the first several modes. Fluid-structure coupling is performed for a highly skewed propeller. The computing time for the dynamic mesh by the present method is about 0.017% of the computing time by the existing elastic solid method. The computing time for the fluid-structure coupling using the present method is 52% less than the computing time by the existing elastic solid method.